Morindone from Morinda citrifolia as a potential antiproliferative agent against colorectal cancer cell lines - Chee, Cheok Wui; Nor Hisam, Zamakshshari; Vannajan Sanghiran, Lee; Iskandar, Abdullah; Rozana, Othman; Lee, Yean Kee; Najihah, Mohd Hashim; Nurshamimi, Nor RashidI (PLOS, 2022)
There is an increasing demand in developing new, effective, and affordable anti-cancer against colon and rectal. In this study, our aim is to identify the potential anthraquinone compounds from the root bark of Morinda citrifolia to be tested in vitro against colorectal cancer cell lines. Eight potential anthraquinone compounds were successfully isolated, purified and tested for both in-silico and in-vitro analyses. Based on the in-silico prediction, two anthraquinones, morindone and rubiadin, exhibit a comparable binding affinity towards multitargets of β-catenin, MDM2-p53 and KRAS. Subsequently, we constructed a 2D interaction analysis based on the above results and it suggests that the predicted anthraquinones from Morinda citrifolia offer an attractive starting point for potential antiproliferative agents against colorectal cancer. In vitro analyses further indicated that morindone and damnacanthal have significant cytotoxicity effect and selectivity activity against colorectal cancer cell lines.